Community Pharmacists’ Perception about Mental Healthcare and Barriers to providing Pharmaceutical Care Services to Patients with Mental Disorder in Ibadan, Nigeria (2023)
Community pharmacists play a significant role by providing pharmaceutical care for patients with mental disorders. Mental disorder is a health priority in national health strategies around the world, including in Nigeria. However, personal perception and practice-related barriers may prevent full involvement. This study therefore aims to assess community pharmacists’ perception and level of comfort towards mental healthcare, as well as the barriers in providing pharmaceutical care to patients with mental disorder in Ibadan. A cross-sectional study among 120 community pharmacists in Ibadan, using a self-administered questionnaire. Descriptive statistics including frequency and percentage were used to summarize the data. The majority (99;82.5%) agreed they will deal with mentally ill patients, while 81 (67.5%) feel confident and comfortable to provide pharmaceutical care to patients with mental illness. Major barriers to pharmaceutical care cited includes inability to monitor outcomes as patients may never return to the pharmacy again (88; 73.3%) and having only limited patient information (85;70.8%). This corresponds with the revelation that (88; 73.3%) believe that follow up for adverse drug related problem is not easy. About 23% community pharmacies do not stock psychotropic medication at all, mainly due to few requests and tough regulations of record keeping required by law. Despite willingness to provide services to patients with mental illness, reduced stockings of psychotropics and practice-related barriers prevent full participation of community pharmacists.